Femmes et droit public Liberté, égalité, sororité - Humbert, Marion; Martins, Maverick; Routier, Romain (Schol@, 2023)
For their second study day, the Association des Publicistes Palois invited law students from the Université de Pau et des pays de l'Adour to meet around a unifying theme: "Women and Public Law: Liberty, Equality, Sisterhood". The proceedings of this day are gathered in this book. This event was an opportunity to address current issues around new questions, such as menstrual precariousness, or renewed questions, such as parity. This conference allowed UPPA students to participate for the first time in a scientific production in law.